Implementasi Profil Pelajar Pancasila dalam Pembelajaran IPAS Siswa Kelas IV SDN 1 Kota Bengkulu - Sulistyani, Shelomitha; Dalifa; Yusnia (Universitas Bengkulu, 2025)
Th.is study a.ims to describe the implementation of the Pancasila learner profile in the planning and implementation of IPAS learning for fourth grade students of SDN 1 Bengkulu City. Th.is rese.a.rch method is descriptive qualitative. The primary data of the research was obtained from observatio.n guidelines, interview guidelines conducted directly to data sources, namely class IV/B homeroom teacher, principal, deputy curriculum, and class IV/B students of SDN 1 Bengkulu City. Secondary data used i.n the form of photo documentation, videos, and sound recordings. The data were collected t.hroug.h observation, interviews, and documentation. Data analysis techniques by collecting data, data reduc.t.io.n, data presentation, and conclusion drawing. The research results of the implementation of t.h.e P.ancas.il.a student profile in IPAS learning for grade IV students of SDN 1 Bengkulu City show that in (1) planning, it has been implemented with t.he Pa.ncas.il.a s.tude.nt character which can be seen in each component of the teaching module. The di.m.ens.ion o.f t.he Pan.casi.la learner profile that appears most in the planning of the IPAS learning teaching module is critical reasoning. (2) implementation, has been implemented with th.e cha.ract.er of Panc.asila stu.dents which can be seen in 3 stages of activities, namely opening, core, and closing. The dimension o.f t.he Pan.casi.la s.tud.ent pr.ofi.le that appears most in the implementation of IPAS learning is critical reasoning. For dimensions that appear less in learning is global diversity.